Timur Tengah: Pusat Pengembangan Paham Keagamaan di Indonesia - Supani Supani (STAI ALHIKMAH Jakarta, 2016)
Abstract Makkah and Madinah are the center of islamic religious understanding development which is continuously developed by Ulama through networks in different areas of Islam, included Indonesia. The transmission proses of religious understanding always involves with local tradition which has already existed before in the place where Islam come. Islam develops in Indonesia peaceful and evolutionary. However, contact period of peace and harmony with Islam is disrupted by internal religious conflicts between the ortodox and heterodox sufi stream. Keywords: Middle East, Religious Understanding, Indonesia Abstrak Makkah dan Madinah merupakan pusat perkembangan paham keagamaan Islam yang secara terus-menerus dikembangkan oleh para ulama melalui jaringannya ke berbagai wilayah Islam, termasuk di Indonesia. Proses transmisi paham keagamaan tersebut selalu bersinggungan dengan tradisi lokal yang telah ada sebelumnya di tempat di mana Islam datang. Islam berkembang di Indonesia dengan damai dan evolusioner. Namun, periode kontak yang damai dan harmonis dengan Islam tersebut kemudian terganggu oleh konflik-konflik keagamaan internal antara kaum sufi aliran ortodoks dan aliran heterodoks Kata Kunci: Timur Tengah, Paham Keagamaan, Indonesia